miR-335 Acts as a Tumor Suppressor and Enhances Ionizing Radiation-Induced Tumor Regression by Targeting ROCK1 - Cheng, Yanfeng; Shen, Peng (Frontiers in Oncology, 2020)
Recent development of integrative therapy against melanoma combines surgery, radiotherapy, targeted therapy, and immunotherapy; however, the clinical outcomes of advanced stage and recurrent melanoma are poor. As a skin cancer, melanoma is generally resistant to radiotherapy. Hence, there is an urgent need for evaluation of the mechanisms of radioresistance. The present study identified miR-335 as one of the differential expression of miRNAs in recurrent melanoma biopsies post-radiotherapy. The expression of miR-335 declined in melanoma tissues compared to the adjacent tissues. Moreover, miR-335 expression correlated with advanced stages of melanoma negatively. Consistent with the prediction of STARBASE and miRDB database, miR-335 targeted ROCK1 via binding with 3’-UTR of ROCK1 directly, resulting in attenuation of proliferation, migration, and radioresistance of melanoma cells. The authors validated that overexpression of miR-335 enhanced X-ray-induced tumor regression by B16 mouse models. Briefly, the present findings gained insights into miR-335/ROCK1-mediated radiosensitivity and provided a promising therapeutic strategy for improving radiotherapy against melanoma.